Education and training of emergency nursing - Witold Pawłowski; Dorota Lasota; Krzysztof Goniewicz; Mariusz Goniewicz; Patrycja Misztal-Okońska (Kazimierz Wielki University, 2018)
In recent years, rapid changes taking place in the system of medical emergency services, as well as in emergency nursing, have contributed to changes of binding legislation. Amendment of the regulation of the Minister of Health and Social Welfare on postgraduate education of nurses and midwives concerned the extension of domains' list by emergency nursing, which has resulted in the organisation of specialist and training in the field of emergency nursing since 2004. The objective of the following paper is to present new regulations normalising education of nurses, with a detailed specialist curriculum "Performing tracheotomy: the decompression of tension pneumothorax and intraosseous access" as well as the nurse's rights in the field of diagnostics and therapeutic services